A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth

By using coating materials containing casting materials, graphite, phosphoric acid, silicon carbide and flossil on the Mannheim furnace rake teeth, combined with specific construction methods, the problem of corrosion and oxidation of the Mannheim furnace rake teeth is solved, and the effect of enhancing adhesion and crack resistance is achieved, extending the use time and reducing maintenance costs.

CN119775808APending Publication Date: 2025-04-08QINGDAO SODA ASH IND DEV CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411976029.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The Mannheim furnace rake teeth are prone to corrosion during high-temperature corrosion and oxidation, resulting in shedding and furnace shutdown and overhaul. The existing coating materials lack crack resistance and oxidation resistance, poor adhesion, and cracks are easily generated due to changes in temperature difference.

Method used

Using a coating material including casting materials, graphite, phosphoric acid, silicon carbide and flossil, a stable protective layer is formed to enhance adhesion and crack resistance through specific construction methods such as ball milling, stirring, heat treatment and welding hook nails.

Benefits of technology

Effectively prevent corrosion and oxidation of the Mannheim furnace rake teeth, enhance adhesion and adhesion, avoid cracks due to temperature differences, extend the use time of the furnace parts, and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a coating material for preventing Mannheim furnace rake teeth from corrosion and oxidation. The coating material comprises the following components in percentage by mass: casting material: 40%-60%; graphite: 10%-20%; phosphoric acid: 5%-15%; silicon carbide: 5%-15%; sodium carbonate: 5%-10%. The invention improves the high temperature resistance of the coating material by adding graphite to the coated casting material, increases the bonding force and adhesion of the coating material by adding phosphoric acid, and improves the thermal conductivity and expansion coefficient of the coating material by adding silicon carbide material, so that the temperature of the coating material is close to that of furnace internals and cracks will not occur due to large temperature differences. The coating material is comprehensively improved in terms of crack resistance, oxidation resistance, and high temperature resistance, and can enhance bonding force and adhesion, relieve radial tension caused by temperature changes, and does not generate cracks. The coating material has a similar expansion coefficient to that of furnace internals, can expand simultaneously when heated, and is well bonded together without falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical equipment protection, and in particular relates to a coating material for preventing Mannheim furnace rake teeth from being corroded and oxidized. Background Art

[0002] Mannheim furnace is the main equipment for producing potassium sulfate. Sulfuric acid and potassium chloride are added into the Mannheim furnace in a certain proportion, and potassium sulfate and hydrogen chloride are generated through high-temperature reaction. Potassium sulfate is pushed to the discharge port through the reaction zone and drying zone under the push of the stirring rake. The internal parts of conventional Mannheim furnace are mainly stirring rake teeth and large arms, salt pans, acid pans, etc. Once the internal parts of the furnace are corroded, the stirring rake teeth fall off, and the materials in the furnace cannot be pushed, the furnace needs to be stopped for overhaul, so the service life of the stirring rake teeth, large arms and other furnace internal parts is crucial.

[0003] In the prior art, although some coating materials have been used for protection, they still have problems such as insufficient crack resistance and oxidation resistance, poor adhesion, and easy cracking due to temperature changes.

[0004] Based on this, a coating material is designed to prevent corrosion and oxidation of Mannheim furnace rake teeth. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a coating material for preventing the corrosion and oxidation of the rake teeth of the Mannheim furnace, which effectively solves the problems raised in the above background.

[0006] To achieve the above object, the present invention provides the following technical solution: a coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in mass percentage:

[0007] Casting material: 40%-60%;

[0008] Graphite: 10%-20%;

[0009] Phosphoric acid: 5%-15%;

[0010] Silicon carbide: 5%-15%;

[0011] Sodium carbonate: 5%-10%.

[0012] Preferably, the construction method of the coating material comprises the following steps:

[0013] Step S1, raw material preparation:

[0014] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0015] S1.2, then use a ball mill to grind the raw materials at room temperature for 2-4 hours to crush them to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0016] Step S2, mixing and stirring:

[0017] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 30-60 minutes until a uniform slurry is formed;

[0018] Step S3, heating treatment:

[0019] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 5-10°C / min;

[0020] S3.2, heat to 80-120℃ and maintain this temperature for 2-4h to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0021] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0022] Step S4, coating construction:

[0023] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure that the surface is clean and flat;

[0024] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.5-1mm, and dry it naturally at room temperature for 24-36 hours until a firm bonding layer is formed;

[0025] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1-2 mm.

[0026] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0027] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1-2 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 48-60 hours;

[0028] Step S5, final curing:

[0029] Place the coated furnace internals in a heating furnace, heat to 150-200°C at a heating rate of 2-5°C / min, and maintain for 4-6 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0030] Preferably, in step S1, during the mixing process, the temperature is 60-80°C, the stirring rate is 350-500 rpm, and the stirring time is 30-50 min.

[0031] Preferably, in step S2, the concentration of phosphoric acid is 15%-20%, and the rotation speed of the stirrer is 100-150 rpm.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention improves the high temperature resistance of the coating material by adding graphite to the coated casting material, increases the bonding force and adhesion of the coating material by adding phosphoric acid, and improves the thermal conductivity and expansion coefficient of the coating material by adding silicon carbide material, so that the temperature of the coating material is close to that of the furnace internals, and cracks will not form due to large temperature differences. The coating material's crack resistance, oxidation resistance, and high temperature resistance are comprehensively improved, and the bonding force and adhesion can be enhanced, and the radial tension caused by temperature changes can be alleviated without cracks. The coating material has a similar expansion coefficient to the furnace internals, and can expand simultaneously when the temperature rises, and is well bonded together without falling off;

[0034] 2. During construction, the present invention applies a phosphoric acid binder to the inner layer, which can increase adhesion and react with the casting material at high temperature to solidify, and is integrated without displacement gaps. By welding hooks, the coating material is firmly combined with the furnace internals and does not fall off. The outer layer is coated with sodium silicate slurry, so that the surface layer deforms softly when it starts to heat up, and cracks are better prevented;

[0035] 3. The present invention adds coating materials on the surface of furnace internals, which expands simultaneously with the rise and fall of temperature without generating cracks or falling off due to temperature changes. The furnace internals are effectively protected and the service life of the furnace internals is extended. There is no need to stop production and overhaul due to corrosion of the furnace internals, thus saving maintenance costs. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] The present invention provides a coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in percentage by mass:

[0038] Casting material: 40%-60%, as the main material, providing good physical strength and wear resistance;

[0039] Graphite: 10%-20%, enhances the high temperature resistance and lubricity of the coating material and reduces friction;

[0040] Phosphoric acid: 5%-15%, as a binder, increases the adhesion between the coating material and the furnace internals and promotes curing;

[0041] Silicon carbide: 5%-15%, improves thermal conductivity and expansion coefficient matching, and reduces cracks caused by temperature differences;

[0042] Sodium carbonate: 5%-10%, used for outer coating to increase the flexibility and crack resistance of the coating.

[0043] The construction method of the coating material of this embodiment comprises the following steps:

[0044] Step S1, raw material preparation:

[0045] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0046] S1.2, then use a ball mill to grind the raw materials at room temperature for 2-4 hours to crush them to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0047] Step S2, mixing and stirring:

[0048] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 30-60 minutes until a uniform slurry is formed;

[0049] Step S3, heating treatment:

[0050] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 5-10°C / min;

[0051] S3.2, heat to 80-120℃ and maintain this temperature for 2-4h to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0052] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0053] Step S4, coating construction:

[0054] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure a clean and smooth surface;

[0055] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.5-1mm, and dry it naturally at room temperature for 24-36 hours until a firm bonding layer is formed;

[0056] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1-2 mm.

[0057] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0058] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1-2 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 48-60 hours;

[0059] Step S5, final curing:

[0060] Place the coated furnace internals in a heating furnace, heat to 150-200°C at a heating rate of 2-5°C / min, and maintain for 4-6 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0061] In step S1 of this embodiment, during the mixing process, the temperature is 60-80° C., the stirring rate is 350-500 rpm, and the stirring time is 30-50 min.

[0062] In step S2 of this embodiment, the concentration of phosphoric acid is 15%-20%, and the rotation speed of the stirrer is 100-150 rpm.

[0063] Embodiment 1:

[0064] A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in mass percentage:

[0065] Casting material: 40%;

[0066] Graphite: 10%;

[0067] Phosphoric acid: 5%;

[0068] Silicon carbide: 5%;

[0069] Sodium carbonate: 5%.

[0070] The construction method of the coating material of this embodiment comprises the following steps:

[0071] Step S1, raw material preparation:

[0072] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0073] S1.2, then use a ball mill to grind the raw materials at room temperature for 2 h to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0074] Step S2, mixing and stirring:

[0075] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 30 minutes until a uniform slurry is formed;

[0076] Step S3, heating treatment:

[0077] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 5°C / min;

[0078] S3.2, heat to 80°C and maintain this temperature for 2 hours to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0079] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0080] Step S4, coating construction:

[0081] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure a clean and smooth surface;

[0082] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.5 mm, and dry it naturally at room temperature for 24 hours until a firm bonding layer is formed;

[0083] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1 mm.

[0084] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0085] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 48 hours;

[0086] Step S5, final curing:

[0087] Place the coated furnace internals in a heating furnace, heat to 150°C at a heating rate of 2°C / min, and maintain for 4 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0088] In step S1 of this embodiment, during the mixing process, the temperature is 60° C., the stirring rate is 350 rpm, and the stirring time is 30 min.

[0089] In step S2 of this embodiment, the concentration of phosphoric acid is 15%, and the rotation speed of the stirrer is 100 rpm.

[0090] Embodiment 2:

[0091] A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in mass percentage:

[0092] Casting material: 60%;

[0093] Graphite: 20%;

[0094] Phosphoric acid: 15%;

[0095] Silicon carbide: 15%;

[0096] Sodium carbonate: 10%.

[0097] The construction method of the coating material of this embodiment comprises the following steps:

[0098] Step S1, raw material preparation:

[0099] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0100] S1.2, then use a ball mill to grind the raw materials at room temperature for 4 hours to crush them to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0101] Step S2, mixing and stirring:

[0102] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 60 minutes until a uniform slurry is formed;

[0103] Step S3, heating treatment:

[0104] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 10°C / min;

[0105] S3.2, heat to 120°C and maintain this temperature for 4 hours to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0106] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0107] Step S4, coating construction:

[0108] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure a clean and smooth surface;

[0109] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 1 mm, and dry it naturally at room temperature for 36 hours until a firm bonding layer is formed;

[0110] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 2 mm.

[0111] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0112] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 2 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 60 hours;

[0113] Step S5, final curing:

[0114] Place the coated furnace internals in a heating furnace, heat to 200°C at a heating rate of 5°C / min, and maintain for 6 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0115] In step S1 of this embodiment, during the mixing process, the temperature is 80° C., the stirring rate is 500 rpm, and the stirring time is 50 min.

[0116] In step S2 of this embodiment, the concentration of phosphoric acid is 20%, and the rotation speed of the stirrer is 150 rpm.

[0117] Embodiment 3:

[0118] A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in mass percentage:

[0119] Casting material: 50%;

[0120] Graphite: 15%;

[0121] Phosphoric acid: 10%;

[0122] Silicon carbide: 10%;

[0123] Sodium carbonate: 7.5%.

[0124] The construction method of the coating material of this embodiment comprises the following steps:

[0125] Step S1, raw material preparation:

[0126] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0127] S1.2, then use a ball mill to grind the raw materials at room temperature for 3 hours to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0128] Step S2, mixing and stirring:

[0129] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 45 minutes until a uniform slurry is formed;

[0130] Step S3, heating treatment:

[0131] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 7.5°C / min;

[0132] S3.2, heat to 100°C and maintain this temperature for 3 hours to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0133] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0134] Step S4, coating construction:

[0135] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure a clean and smooth surface;

[0136] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.75 mm, and dry it naturally at room temperature for 30 hours until a firm bonding layer is formed;

[0137] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1.5 mm.

[0138] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0139] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1.5 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 54 hours;

[0140] Step S5, final curing:

[0141] The coated furnace internals are placed in a heating furnace and heated to 175°C at a heating rate of 3.5°C / min and maintained for 5 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0142] In step S1 of this embodiment, during the mixing process, the temperature is 70° C., the stirring rate is 425 rpm, and the stirring time is 45 min.

[0143] In step S2 of this embodiment, the concentration of phosphoric acid is 17.5%, and the rotation speed of the stirrer is 125 rpm.

[0144] Embodiment 4:

[0145] A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, comprising the following components in mass percentage:

[0146] Casting material: 45%;

[0147] Graphite: 13%;

[0148] Phosphoric acid: 8%;

[0149] Silicon carbide: 8%;

[0150] Sodium carbonate: 7%.

[0151] The construction method of the coating material of this embodiment comprises the following steps:

[0152] Step S1, raw material preparation:

[0153] S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio;

[0154] S1.2, then use a ball mill to grind the raw materials at room temperature for 2.5 hours to crush them to a fineness of less than 100 mesh to ensure that all components are fully dispersed;

[0155] Step S2, mixing and stirring:

[0156] After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 35 minutes until a uniform slurry is formed;

[0157] Step S3, heating treatment:

[0158] S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 6°C / min;

[0159] S3.2, heat to 90°C and maintain this temperature for 2.5 hours to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force;

[0160] S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction;

[0161] Step S4, coating construction:

[0162] S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure a clean and smooth surface;

[0163] S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.6 mm, and dry it naturally at room temperature for 28 hours until a firm bonding layer is formed;

[0164] S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1.2 mm.

[0165] S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals;

[0166] S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1.2 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 50 hours;

[0167] Step S5, final curing:

[0168] The coated furnace internals are placed in a heating furnace and heated to 165°C at a heating rate of 3°C / min and maintained for 4.5 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

[0169] In step S1 of this embodiment, during the mixing process, the temperature is 65° C., the stirring rate is 400 rpm, and the stirring time is 35 min.

[0170] In step S2 of this embodiment, the concentration of phosphoric acid is 16%, and the rotation speed of the stirrer is 110 rpm.

[0171] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0172] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth, characterized in that: The following ingredients are included in mass percentage: Casting material: 40%-60%; Graphite: 10%-20%; Phosphoric acid: 5%-15%; Silicon carbide: 5%-15%; Sodium carbonate: 5%-10%.

2. A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth according to claim 1, characterized in that: The construction method of the coating material comprises the following steps: Step S1, raw material preparation: S1.1, uniformly mix the casting material, graphite, phosphoric acid and silicon carbide according to the above mass percentage ratio; S1.2, then use a ball mill to grind the raw materials at room temperature for 2-4 hours to crush them to a fineness of less than 100 mesh to ensure that all components are fully dispersed; Step S2, mixing and stirring: After mixing the above solid raw materials in proportion, add phosphoric acid and an appropriate amount of water, and stir in a stirrer at room temperature for 30-60 minutes until a uniform slurry is formed; Step S3, heating treatment: S3.1, placing the uniformly mixed slurry in a heating furnace and heating it at a heating rate of 5-10°C / min; S3.2, heat to 80-120℃ and maintain this temperature for 2-4h to ensure that the chemical reaction in the slurry is fully carried out, forming a stable structure and enhancing the bonding force; S3.3, after heating is completed, the slurry is allowed to cool naturally to room temperature and is ready for the next step of coating construction; Step S4, coating construction: S4.1, before coating, the furnace internals must be thoroughly cleaned and pre-treated to remove oil, dust and rust impurities on the surface to ensure that the surface is clean and flat; S4.2, then evenly apply the phosphoric acid adhesive on the surface of the furnace internals with a thickness of 0.5-1mm, and dry it naturally at room temperature for 24-36 hours until a firm bonding layer is formed; S4.3, apply the treated slurry evenly and continuously on the bonding layer on the surface of the furnace internals, with a coating thickness of 1-2 mm. S4.4, before the coating is completely dry, use welding technology to evenly weld hook nails on the coating, and the length of the hook nails shall not exceed 2 / 3 of the total thickness of the coating to enhance the bonding strength between the coating and the furnace internals; S4.5, then, apply sodium silicate slurry on the outer layer with a thickness of 1-2 mm, and further prevent cracks from occurring by virtue of the soft deformation characteristics of sodium silicate. After coating, dry naturally at room temperature for 48-60 hours; Step S5, final curing: Place the coated furnace internals in a heating furnace, heat to 150-200°C at a heating rate of 2-5°C / min, and maintain for 4-6 hours to complete the final curing, ensuring that the coating layer is tightly bonded to the furnace internals to form a stable protective layer.

3. A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth according to claim 2, characterized in that: In step S1, during the mixing process, the temperature is 60-80° C., the stirring rate is 350-500 rpm, and the stirring time is 30-50 min.

4. A coating material for preventing corrosion and oxidation of Mannheim furnace rake teeth according to claim 2, characterized in that: In step S2, the concentration of phosphoric acid is 15%-20%, and the rotation speed of the stirrer is 100-150 rpm.